A Review of Infections After Hematopoietic Cell Transplantation Requiring PICU Care: Transplant Timeline Is Key - Ferdjallah, Asmaa; Young, Jo-Anne H.; MacMillan, Margaret L. (Frontiers in Pediatrics, 2021)
Despite major advances in antimicrobial prophylaxis and therapy, opportunistic infections remain a major cause of morbidity and mortality after hematopoietic cell transplant (HCT) for children. Risk factors associated with the development of opportunistic infections include the patient’s underlying disease, previous infections, co-morbidities, donor graft, preparative therapy, immunosuppressive agents, toxicities after transplant and graft-versus-host disease (GVHD). Additionally, the risk and type of infection changes throughout the HCT course and is greatly influenced by the degree and duration of immunosuppression of the HCT recipient. All HCT recipients are at high risk for rapid clinical decompensation, and the pediatric intensivist must remain abreast of the status of the immune system in relation to transplant. This review will serve to highlight the shifting infection risks during the HCT process and to provide key clinical considerations for the pediatric intensivist by presenting a series of HCT cases.